A high-toughness epoxy resin coating and preparation process

By using components such as sulfur-modified benzoxazines in epoxy resin coatings and adopting specific processes, the problem of insufficient toughness and hardness of existing coatings when improving flame retardancy and antibacterial effects has been solved, achieving high Flame retardant, antibacterial and good mechanical properties.

CN118755360BActive Publication Date: 2025-01-24JUNXIU NEW MATERIAL TECH (SUZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410991367.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-01-24
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

While existing epoxy resin coatings have not effectively improved their toughness and hardness while improving flame retardancy and antibacterial effects.

Method used

Use bisphenol -A -type epoxy resin, sulfur -containing benzene, titanium pink powder, talc powder, foaming agent, and humid dispersion agent to prepare high -tough epoxy resin through specific stirring and reaction processes coating.

Benefits of technology

It achieves high flame retardancy and antibacterial effects of the coating, while significantly improving its toughness, hardness and gloss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004958961080000081
    Figure BDA0004958961080000081
  • Figure BDA0004958961080000091
    Figure BDA0004958961080000091
Patent Text Reader

Abstract

The present invention relates to the technical field of coatings, and discloses a high-toughness epoxy resin coating and a preparation process. The present invention is prepared by adding bisphenol A epoxy resin, triethylenetetramine, sulfur-modified benzoxazine, titanium dioxide, talcum powder, BYK-071 defoamer, BYK-345 leveling agent, and BYK-220S wetting dispersant into a stirrer, stirring, and obtaining a high-toughness epoxy resin coating after the end. The carbon nanotubes in the sulfur-modified benzoxazine have flame retardant properties and hardness, wherein the sulfur element has a good flame retardant effect; during the heating process, the sulfur-modified benzoxazine will undergo a ring-opening reaction with the epoxy groups in the bisphenol A epoxy resin, forming a cross-linked network between each other, making it tighter, and at the same time, the side chains of the sulfur-modified benzoxazine themselves will also be entangled with the bisphenol A epoxy resin, thereby increasing the toughness of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a high-toughness epoxy resin coating and a preparation process. Background Art

[0002] Epoxy resin has excellent adhesion, electrical insulation, mechanical strength and other characteristics, and is widely used in the fields of coatings, adhesives, etc. However, epoxy resin is flammable, which limits its application in coatings. Therefore, how to improve its toughness and flame retardancy is the key to solving the problem; for example, patent CN106867366B discloses a high-efficiency flame-retardant epoxy resin coating. The high-efficiency flame-retardant epoxy resin coating provided by the present invention has a reasonable formula, and a nitrogen-phosphorus-containing surface-migrating flame retardant is added to the coating system. On the one hand, the flame retardant has strong surface mobility and can form a high flame-retardant film on the surface of the substrate with good flame retardant effect, but its toughness is not improved. Summary of the invention

[0003] 1. Technical issues to be solved

[0004] In view of the deficiencies of the prior art, the present invention provides a high-toughness epoxy resin coating and a preparation process, which has good flame retardant and antibacterial effects, as well as good toughness, hardness and glossiness.

[0005] (II) Technical solution

[0006] To achieve the above object, the present invention provides the following technical solution: a high-toughness epoxy resin coating, comprising the following components by weight: 30-50 parts by weight of bisphenol A epoxy resin, 2-4 parts by weight of triethylenetetramine, 5-8 parts by weight of sulfur-modified benzoxazine, 1-3 parts by weight of titanium dioxide, 2-5 parts by weight of talc, 0.7-1 parts by weight of BYK-071 defoamer, 0.4-0.8 parts by weight of BYK-345 leveling agent, and 0.6-0.8 parts by weight of BYK-220S wetting and dispersing agent.

[0007] Preferably, the preparation process of the sulfur-containing modified benzoxazine is:

[0008] (1) 5-8 parts by weight of 2-(dimethylamino)ethyl methacrylate, 6-10 parts by weight of dodecafluoroheptyl methacrylate, 7-10 parts by weight of 3-mercapto-1,2-propylene glycol, 5-8 parts by weight of olefinated carbon nanotubes, and 1-2 parts by weight of azobisisobutyronitrile are added to a three-necked flask equipped with a condensation reflux device, and then 1,4-butylene oxide solvent is added, nitrogen is introduced for protection, and the reaction is carried out at 75-90° C. for 10-15 hours. After the reaction is completed, the excess solvent is removed by a rotary evaporator, and then the product is precipitated in excess n-hexane, the unreacted small molecular monomer is removed, the supernatant is poured off, and the mixture is dried at 50-75° C. for 20-24 hours to obtain an intermediate 1;

[0009] (2) adding 2-bromoethanol and intermediate 1 to isopropanol solvent, and refluxing at 65-80° C. for 30-40 h. After the reaction, rotary evaporation is performed, and ethanol is recrystallized to obtain intermediate 2;

[0010] (3) Add intermediate 2 and p-methoxybenzoyl chloride to N,N-dimethylformamide solvent, stir to dissolve, continue to add pyridine catalyst, react at 30-60° C. for 8-15 hours, concentrate the solvent, wash with acetone, and dry to obtain intermediate 3;

[0011] (4) Add N,N-dimethylformamide and intermediate 3 to a reaction flask, add boron tribromide dropwise at -15 to -18°C, react for 12 to 20 hours, then add methanol dropwise to terminate the reaction, filter, wash with acetone, and recrystallize with ethyl acetate to obtain a phenol-based polymer;

[0012] (5) Add 7-12 parts by weight of a phenol-based polymer, 5-10 parts by weight of aniline, and 12-16 parts by weight of a formaldehyde aqueous solution to a reaction bottle, condense and reflux at 60-85° C., stir evenly, add an oxalic acid catalyst, react for 4-8 hours, add water after reaction, let stand and separate, filter and dry to obtain a sulfur-modified benzoxazine; the mass fraction of the formaldehyde aqueous solution is 40%.

[0013] Preferably, the preparation process of the olefinated carbon nanotubes in (1) is:

[0014] S1. 5-9 parts by weight of hydroxylated carbon nanotubes and 8-14 parts by weight of ε-caprolactone are added to the reactor, stirred evenly, and nitrogen is introduced for protection, and then 0.8-1 parts by weight of stannous octoate catalyst is added, and the reaction is carried out at 110-135 ° C for 6-10h. After the reaction is completed, the crude product is first dissolved with chloroform, and then precipitated with anhydrous ether, and the dissolution and precipitation are repeated 3-5 times, and dried to obtain caprolactone-modified carbon nanotubes;

[0015] S2. Add 6-13 parts by weight of caprolactone-modified carbon nanotubes and 10-16 parts by weight of acryloyl chloride to N,N-dimethylformamide solvent, disperse by ultrasonication, and then continue to add 0.4-0.8 parts by weight of pyridine catalyst, react at 75-90°C for 6-12 hours, and then distill under reduced pressure, filter and dry to obtain olefinated carbon nanotubes.

[0016] Preferably, the mass ratio of 2-bromoethanol to intermediate 1 in (2) is 1.4-1.8:1.

[0017] Preferably, the mass ratio of the intermediate 2, p-methoxybenzoyl chloride and pyridine catalyst in (3) is 1:0.8-1.3:0.01-0.02.

[0018] Preferably, the mass ratio of the intermediate 3 to boron tribromide in (4) is 1:0.7-1.

[0019] Preferably, the preparation process of the high-toughness epoxy resin coating is: add bisphenol A epoxy resin, triethylenetetramine, sulfur-modified benzoxazine, titanium dioxide, talcum powder, BYK-071 defoamer, BYK-345 leveling agent, BYK-220S wetting dispersant into a stirrer, stir and react at 35-40° C. for 10-15 minutes, and obtain the high-toughness epoxy resin coating after the reaction.

[0020] (III) Beneficial technical effects

[0021] The invention provides a high-toughness epoxy resin coating by adding bisphenol A epoxy resin, triethylenetetramine, sulfur-modified benzoxazine, titanium dioxide, talcum powder, BYK-071 defoamer, BYK-345 leveling agent and BYK-220S wetting dispersant into a stirrer and stirring.

[0022] Hydroxylated carbon nanotubes and ε-caprolactone are reacted under the action of stannous octoate catalyst to obtain caprolactone-modified carbon nanotubes; hydroxyl groups in the caprolactone-modified carbon nanotubes are reacted with acyl chloride in acryloyl chloride to introduce olefinic groups to obtain olefinic carbon nanotubes.

[0023] 2-(Dimethylamino)ethyl methacrylate, dodecafluoroheptyl methacrylate, 3-mercapto-1,2-propylene glycol and olefinic carbon nanotubes are polymerized to obtain intermediate 1; the tertiary amine group in intermediate 1 reacts with bromine in 2-bromoethanol to generate a quaternary ammonium salt and introduces a large number of hydroxyl groups, wherein the quaternary ammonium salt has a good antibacterial effect to obtain intermediate 2, which is further reacted with p-methoxybenzoyl chloride to introduce a methoxy group to obtain intermediate 3, which is then reacted with boron tribromide to introduce phenol to obtain a phenol-based polymer, and finally reacted with aniline and a formaldehyde aqueous solution to obtain a sulfur-modified benzoxazine.

[0024] The carbon nanotubes in the sulfur-modified benzoxazine have flame retardant properties and hardness. The sulfur element can promote the carbonization process of the material during combustion, and the formed carbon layer can effectively block oxygen and heat, thereby improving the flame retardant properties of the coating. The benzoxazine in the sulfur-modified benzoxazine will form a heat-resistant phenolic resin structure at high temperatures, exhibiting a higher thermal decomposition temperature and having a better flame retardant effect. During the heating process, the sulfur-modified benzoxazine will undergo a ring-opening reaction with the epoxy groups in the bisphenol A epoxy resin, forming a cross-linked network between each other to make it tighter. At the same time, the side chains of the sulfur-modified benzoxazine themselves will also be entangled with the bisphenol A epoxy resin, thereby increasing the toughness of the coating. DETAILED DESCRIPTION

[0025] Example 1

[0026] (1) 5 parts by weight of hydroxylated carbon nanotubes and 8 parts by weight of ε-caprolactone were added to a reactor, stirred evenly, and nitrogen was introduced for protection. Then, 0.8 parts by weight of stannous octoate catalyst was added, and the mixture was reacted at 110° C. for 6 hours. After the reaction was completed, the crude product was first dissolved with chloroform, and then precipitated with anhydrous ether. The dissolution and precipitation were repeated 3 times, and then dried to obtain caprolactone-modified carbon nanotubes;

[0027] (2) Add 6 parts by weight of caprolactone-modified carbon nanotubes and 10 parts by weight of acryloyl chloride to N,N-dimethylformamide solvent, disperse by ultrasonication, and then continue to add 0.4 parts by weight of pyridine catalyst, react at 75° C. for 6 hours, and then distill under reduced pressure, filter and dry to obtain olefinated carbon nanotubes.

[0028] (3) 5 parts by weight of 2-(dimethylamino)ethyl methacrylate, 6 parts by weight of dodecafluoroheptyl methacrylate, 7 parts by weight of 3-mercapto-1,2-propanediol, 5 parts by weight of olefinated carbon nanotubes, and 1 part by weight of azobisisobutyronitrile were added to a three-necked flask equipped with a condensation reflux device, and then 1,4-butylene oxide solvent was added, nitrogen was introduced for protection, and the reaction was carried out at 75° C. for 10 hours. After the reaction was completed, the excess solvent was removed by a rotary evaporator, and then the product was precipitated in excess n-hexane, the unreacted small molecular monomers were removed, the supernatant was poured out, and the mixture was dried at 50° C. for 20 hours to obtain intermediate 1;

[0029] (4) adding 2-bromoethanol and intermediate 1 to isopropanol solvent, wherein the mass ratio of 2-bromoethanol to intermediate 1 is 1.4:1, and refluxing at 65° C. for 30 h. After the reaction, rotary evaporation is performed and ethanol is recrystallized to obtain intermediate 2;

[0030] (5) adding intermediate 2 and p-methoxybenzoyl chloride to N,N-dimethylformamide solvent, stirring to dissolve, and continuing to add pyridine catalyst, wherein the mass ratio of intermediate 2, p-methoxybenzoyl chloride, and pyridine catalyst is 1:0.8:0.01, reacting at 30° C. for 8 h, concentrating the solvent, washing with acetone, and drying to obtain intermediate 3;

[0031] (6) Add N,N-dimethylformamide and intermediate 3 to a reaction flask, add boron tribromide dropwise at -15°C, wherein the mass ratio of intermediate 3 to boron tribromide is 1:0.7, react for 12 hours, then add methanol dropwise to terminate the reaction, filter, wash with acetone, and recrystallize with ethyl acetate to obtain a phenol-based polymer;

[0032] (7) Add 7 parts by weight of a phenol-based polymer, 5 parts by weight of aniline, and 12 parts by weight of a formaldehyde aqueous solution to a reaction bottle, condense and reflux at 60° C., stir evenly, add oxalic acid catalyst, react for 4 hours, add water after reaction, let stand for stratification, filter and dry to obtain a sulfur-modified benzoxazine;

[0033] (8) 30 parts by weight of bisphenol A epoxy resin, 2 parts by weight of triethylenetetramine, 5 parts by weight of sulfur-modified benzoxazine, 1 part by weight of titanium dioxide, 2 parts by weight of talc, 0.7 parts by weight of BYK-071 defoamer, 0.4 parts by weight of BYK-345 leveling agent, and 0.6 parts by weight of BYK-220S wetting and dispersing agent were added into a stirrer, and the mixture was stirred and reacted at 35° C. for 10 minutes to obtain a high-toughness epoxy resin coating.

[0034] Example 2

[0035] (1) 9 parts by weight of hydroxylated carbon nanotubes and 14 parts by weight of ε-caprolactone were added to a reactor, stirred evenly, and nitrogen was introduced for protection. Then, 1 part by weight of stannous octoate catalyst was added, and the reaction was carried out at 135° C. for 10 hours. After the reaction was completed, the crude product was first dissolved with chloroform and then precipitated with anhydrous ether. The dissolution and precipitation were repeated 5 times, and then dried to obtain caprolactone-modified carbon nanotubes;

[0036] (2) Add 13 parts by weight of caprolactone-modified carbon nanotubes and 16 parts by weight of acryloyl chloride to N,N-dimethylformamide solvent, disperse by ultrasonication, and then continue to add 0.8 parts by weight of pyridine catalyst, react at 90° C. for 12 hours, and then distill under reduced pressure, filter and dry to obtain olefinated carbon nanotubes.

[0037] (3) 8 parts by weight of 2-(dimethylamino)ethyl methacrylate, 10 parts by weight of dodecafluoroheptyl methacrylate, 10 parts by weight of 3-mercapto-1,2-propylene glycol, 8 parts by weight of olefinated carbon nanotubes, and 2 parts by weight of azobisisobutyronitrile were added to a three-necked flask equipped with a condensation reflux device, and then 1,4-butylene oxide solvent was added, nitrogen protection was introduced, and the reaction was carried out at 90° C. for 15 hours. After the reaction was completed, the excess solvent was removed by a rotary evaporator, and then the product was precipitated in excess n-hexane, the unreacted small molecular monomers were removed, the supernatant was poured out, and the mixture was dried at 75° C. for 24 hours to obtain intermediate 1;

[0038] (4) adding 2-bromoethanol and intermediate 1 to isopropanol solvent, wherein the mass ratio of 2-bromoethanol to intermediate 1 is 1.8:1, and refluxing at 80° C. for 40 h. After the reaction, rotary evaporation is performed, and ethanol recrystallization is performed to obtain intermediate 2;

[0039] (5) adding intermediate 2 and p-methoxybenzoyl chloride to N,N-dimethylformamide solvent, stirring to dissolve, and continuing to add pyridine catalyst, wherein the mass ratio of intermediate 2, p-methoxybenzoyl chloride, and pyridine catalyst is 1:1.3:0.02, reacting at 60° C. for 15 h, concentrating the solvent, washing with acetone, and drying to obtain intermediate 3;

[0040] (6) Add N,N-dimethylformamide and intermediate 3 to a reaction flask, add boron tribromide dropwise at -18°C, wherein the mass ratio of intermediate 3 to boron tribromide is 1:1, react for 20 hours, then add methanol dropwise to terminate the reaction, filter, wash with acetone, and recrystallize with ethyl acetate to obtain a phenol-based polymer;

[0041] (7) Add 12 parts by weight of a phenol-based polymer, 10 parts by weight of aniline, and 16 parts by weight of a formaldehyde aqueous solution to a reaction bottle, condense and reflux at 85° C., stir evenly, add oxalic acid catalyst, react for 8 hours, add water after reaction, let stand for stratification, filter and dry to obtain a sulfur-modified benzoxazine;

[0042] (8) 50 parts by weight of bisphenol A epoxy resin, 4 parts by weight of triethylenetetramine, 8 parts by weight of sulfur-modified benzoxazine, 3 parts by weight of titanium dioxide, 5 parts by weight of talc, 1 part by weight of BYK-071 defoamer, 0.8 parts by weight of BYK-345 leveling agent, and 0.8 parts by weight of BYK-220S wetting and dispersing agent were added into a stirrer, and the mixture was stirred and reacted at 40° C. for 15 minutes to obtain a high-toughness epoxy resin coating.

[0043] Example 3

[0044] (1) 7 parts by weight of hydroxylated carbon nanotubes and 11 parts by weight of ε-caprolactone were added to a reactor, stirred evenly, and nitrogen was introduced for protection. Then, 0.9 parts by weight of stannous octoate catalyst was added, and the mixture was reacted at 122.5° C. for 8 hours. After the reaction was completed, the crude product was first dissolved with chloroform and then precipitated with anhydrous ether. The dissolution and precipitation were repeated 4 times, and then dried to obtain caprolactone-modified carbon nanotubes;

[0045] (2) Add 9.5 parts by weight of caprolactone-modified carbon nanotubes and 13 parts by weight of acryloyl chloride to N,N-dimethylformamide solvent, disperse by ultrasonication, and then continue to add 0.6 parts by weight of pyridine catalyst, react at 82.5° C. for 9 hours, and then perform vacuum distillation, filter and dry to obtain olefinated carbon nanotubes.

[0046] (3) 6.5 parts by weight of 2-(dimethylamino)ethyl methacrylate, 8 parts by weight of dodecafluoroheptyl methacrylate, 8.5 parts by weight of 3-mercapto-1,2-propylene glycol, 6.5 parts by weight of olefinated carbon nanotubes, and 1.5 parts by weight of azobisisobutyronitrile were added to a three-necked flask equipped with a condensation reflux device, and then 1,4-butylene oxide solvent was added, and nitrogen was introduced for protection. The reaction was carried out at 82.5° C. for 12.5 hours. After the reaction was completed, the excess solvent was removed by a rotary evaporator, and then the product was precipitated in excess n-hexane, and the unreacted small molecular monomers were removed. The supernatant was poured off and dried at 62.5° C. for 22 hours to obtain intermediate 1;

[0047] (4) adding 2-bromoethanol and intermediate 1 to isopropanol solvent, wherein the mass ratio of 2-bromoethanol to intermediate 1 is 1.6:1, and refluxing at 72.5° C. for 35, and after the reaction, rotary evaporation and ethanol recrystallization are performed to obtain intermediate 2;

[0048] (5) Add intermediate 2 and p-methoxybenzoyl chloride to N,N-dimethylformamide solvent, stir to dissolve, and continue to add pyridine catalyst, wherein the mass ratio of intermediate 2, p-methoxybenzoyl chloride and pyridine catalyst is 1:1.05:0.015, react at 45°C for 11.5h, concentrate the solvent, wash with acetone, and dry to obtain intermediate 3;

[0049] (6) Add N,N-dimethylformamide and intermediate 3 to the reaction flask, add boron tribromide dropwise at -16.5°C, wherein the mass ratio of intermediate 3 to boron tribromide is 1:0.85, react for 16 hours, then add methanol dropwise to terminate the reaction, filter, wash with acetone, and recrystallize with ethyl acetate to obtain a phenol-based polymer;

[0050] (7) Add 9.5 parts by weight of a phenol-based polymer, 7.5 parts by weight of aniline, and 14 parts by weight of a formaldehyde aqueous solution to a reaction bottle, condense and reflux at 72.5° C., stir evenly, add oxalic acid catalyst, react for 6 hours, add water after reaction, let stand for stratification, filter and dry to obtain a sulfur-modified benzoxazine;

[0051] (8) 40 parts by weight of bisphenol A epoxy resin, 3 parts by weight of triethylenetetramine, 6.5 parts by weight of sulfur-modified benzoxazine, 2 parts by weight of titanium dioxide, 3.5 parts by weight of talc, 0.85 parts by weight of BYK-071 defoamer, 0.6 parts by weight of BYK-345 leveling agent, and 0.7 parts by weight of BYK-220S wetting and dispersing agent were added into a stirrer, and the mixture was stirred and reacted at 37.5° C. for 12.5 minutes to obtain a high-toughness epoxy resin coating.

[0052] Comparative Example 1

[0053] (1) 40 parts by weight of bisphenol A epoxy resin, 3 parts by weight of triethylenetetramine, 2 parts by weight of titanium dioxide, 3.5 parts by weight of talc, 0.85 parts by weight of BYK-071 defoamer, 0.6 parts by weight of BYK-345 leveling agent, and 0.7 parts by weight of BYK-220S wetting and dispersing agent were added into a stirrer, and stirred at 37.5° C. for 12.5 minutes to obtain a high-toughness epoxy resin coating.

[0054] Coating performance test.

[0055] The flexibility of the coating film refers to the national standard GB / T1731; the pencil hardness of the coating film refers to the national standard GB / T6739; the gloss test of the coating film refers to the national standard GB / T9754, and the test results are shown in Table 1.

[0056] Table 1: Membrane performance tests.

[0057]

[0058]

[0059] It can be seen from Table 1 that Examples 1-3 of the present invention have better toughness, hardness and glossiness than Comparative Example 1.

[0060] The limiting oxygen index of the material was tested using an oxygen index meter, and the combustion grade of the material was tested using a horizontal and vertical combustion instrument. The test results are shown in Table 2.

[0061] Table 2: Flame retardancy test.

[0062] project Limiting oxygen index (%) Combustion level Example 1 30 V-0 Example 2 33 V-0 Example 3 32 V-0 Comparative Example 1 21 V-1

[0063] It can be seen from Table 2 that Examples 1-3 of the present invention have better flame retardant effects than Comparative Example 1.

[0064] Pipette 1 mL of a 10 8 CFU / mL of Staphylococcus aureus was added to PBS buffer, and then diluted 10-fold to 10 5 CFU / mL, and then add a high-toughness epoxy resin coating sample (1cm×1cm×0.2mm), and then culture it in a constant temperature incubator at 37℃ with shaking for 24h. After culture, add PBS buffer to dilute the bacterial solution 10 times in sequence, and then transfer 0.5mL of the bacterial solution to the agar medium, and continue to culture it at 37℃ with shaking for 24h. After culture, count the colonies and count the antibacterial rate.

[0065] Table 3: Antibacterial performance test.

[0066] project Antibacterial rate (%) Example 1 98.4 Example 2 99.7 Example 3 98.9 Comparative Example 1 82.4

[0067] It can be seen from Table 3 that Examples 1-3 of the present invention have better antibacterial effects than Comparative Example 1.

[0068] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-toughness epoxy resin coating, characterized in that: The invention comprises the following components by weight: 30-50 parts by weight of bisphenol A epoxy resin, 2-4 parts by weight of triethylenetetramine, 5-8 parts by weight of sulfur-modified benzoxazine, 1-3 parts by weight of titanium dioxide, 2-5 parts by weight of talc, 0.7-1 parts by weight of BYK-071 defoamer, 0.4-0.8 parts by weight of BYK-345 leveling agent, and 0.6-0.8 parts by weight of BYK-220S wetting and dispersing agent; The preparation process of the sulfur-containing modified benzoxazine is as follows: (1) 5-8 parts by weight of 2-(dimethylamino)ethyl methacrylate, 6-10 parts by weight of dodecafluoroheptyl methacrylate, 7-10 parts by weight of 3-mercapto-1,2-propylene glycol, 5-8 parts by weight of olefinated carbon nanotubes, and 1-2 parts by weight of azobisisobutyronitrile are added to a three-necked flask equipped with a condensation reflux device, and then 1,4-butylene oxide solvent is added, nitrogen is introduced for protection, and the reaction is carried out at 75-90° C. for 10-15 hours. After the reaction is completed, the excess solvent is removed by a rotary evaporator, and then the product is precipitated in excess n-hexane, the unreacted small molecular monomer is removed, the supernatant is poured off, and the mixture is dried at 50-75° C. for 20-24 hours to obtain an intermediate 1; (2) Add 2-bromoethanol and intermediate 1 to isopropanol solvent, reflux at 65-80°C for 30-40h, and after the reaction, rotary evaporate and recrystallize from ethanol to obtain intermediate 2; (3) Add intermediate 2 and p-methoxybenzoyl chloride to N,N-dimethylformamide solvent, stir to dissolve, continue to add pyridine catalyst, react at 30-60°C for 8-15h, concentrate the solvent, wash with acetone, and dry to obtain intermediate 3; (4) Add N,N-dimethylformamide and intermediate 3 to the reaction flask, add boron tribromide dropwise at -15 to -18°C, react for 12 to 20 hours, then add methanol dropwise to terminate the reaction, filter, wash with acetone, and recrystallize from ethyl acetate to obtain a phenol-based polymer; (5) Add 7-12 parts by weight of a phenol-based polymer, 5-10 parts by weight of aniline, and 12-16 parts by weight of a formaldehyde aqueous solution to a reaction bottle, condense and reflux at 60-85° C., stir evenly, add oxalic acid catalyst, react for 4-8 hours, add water after reaction, let stand to separate, filter and dry to obtain a sulfur-modified benzoxazine; The preparation process of the olefin-containing carbon nanotubes in (1) is as follows: S1. 5-9 parts by weight of hydroxylated carbon nanotubes and 8-14 parts by weight of ε-caprolactone are added to the reactor, stirred evenly, and nitrogen is introduced for protection, and then 0.8-1 parts by weight of stannous octoate catalyst is added, and the reaction is carried out at 110-135 ° C for 6-10h. After the reaction is completed, the crude product is first dissolved with chloroform, and then precipitated with anhydrous ether, and the dissolution and precipitation are repeated 3-5 times, and dried to obtain caprolactone-modified carbon nanotubes; S2. Add 6-13 parts by weight of caprolactone-modified carbon nanotubes and 10-16 parts by weight of acryloyl chloride to N,N-dimethylformamide solvent, disperse by ultrasonication, and then continue to add 0.4-0.8 parts by weight of pyridine catalyst, react at 75-90 ° C for 6-12h, and then distill under reduced pressure, filter and dry to obtain olefinated carbon nanotubes; The mass ratio of 2-bromoethanol to intermediate 1 in (2) is 1.4-1.8:1; The mass ratio of intermediate 2, p-methoxybenzoyl chloride and pyridine catalyst in (3) is 1:0.8-1.3:0.01-0.02; The mass ratio of the intermediate 3 to boron tribromide in (4) is 1:0.7-1.

2. A process for preparing the high-toughness epoxy resin coating as claimed in claim 1, characterized in that: The preparation process of the high-toughness epoxy resin coating is as follows: bisphenol A epoxy resin, triethylenetetramine, sulfur-modified benzoxazine, titanium dioxide, talcum powder, BYK-071 defoamer, BYK-345 leveling agent, and BYK-220S wetting dispersant are added into a stirrer, stirred and reacted at 35-40° C. for 10-15 minutes, and the high-toughness epoxy resin coating is obtained after the reaction.

Citation Information

Patent Citations

  • High-efficiency flame-retardant epoxy resin coatings

    CN106867366B

  • High adhesion, abrasion resistant and anti-corrosive epoxy resin coating

    CN104861819A

  • Carbon nanotube grafted polyvinylidene fluoride copolymer composite dielectric material and preparation method thereof

    CN112592443A